2022
DOI: 10.3390/diagnostics12071684
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Imaging in Diabetic Retinopathy—From the Past to the Present

Abstract: Advancement of imaging technology in retinal diseases provides us more precise understanding and new insights into the diseases’ pathologies. Diabetic retinopathy (DR) is one of the leading causes of sight-threatening retinal diseases worldwide. Colour fundus photography and fluorescein angiography have long been golden standard methods in detecting retinal vascular pathology in this disease. One of the major advancements is macular observation given by optical coherence tomography (OCT). OCT dramatically impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 102 publications
0
3
0
2
Order By: Relevance
“…Recent developments in ultrawide OCT and OCTA equipment has resulted in the ability to image areas measuring 24 × 20 mm, the maximum range currently available among all OCTA devices ( 18 , 19 ). Use of this advanced equipment has shown that the density of the choroidal vessels and the thicknesses of the inner retina segments at the periphery were significantly lower in nonpathological myopic fundi ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in ultrawide OCT and OCTA equipment has resulted in the ability to image areas measuring 24 × 20 mm, the maximum range currently available among all OCTA devices ( 18 , 19 ). Use of this advanced equipment has shown that the density of the choroidal vessels and the thicknesses of the inner retina segments at the periphery were significantly lower in nonpathological myopic fundi ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, high-resolution imaging of the iridocorneal angle (ICA) region and the trabecular meshwork (TM) structures are important for the diagnosis of glaucoma [ 5 , 6 ]. High-resolution imaging of the retina is important for the detection and management of diabetic retinopathy and age-related macular degeneration [ 7 , 8 ]. Several ocular imaging techniques and devices have been developed over the past years for the inspection and imaging of various ocular structures [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fundoscopic imaging is one of the most frequently used methods to assess the interior structures of the eye. In addition to visualizing retinal pathology such as diabetic retinopathy, 1 the resulting images can also be used to measure the distance between retinal structures. For example, in ocular oncology the distances between the optic disk, macula, and tumor are used in radiation treatment planning 2 , 3 ( Fig.…”
mentioning
confidence: 99%